The Influence of Logistics Service Quality on Customer Satisfaction, Trust, Commitment, and Loyalty in the Business to Business (B2B) Context - Chunhabunyatip, Prompassorn; Suwannakoot , Rossukon; Chinchang, Pattarika (Journal of KMITL Business school, 2025)
This study examines the impact of Logistics Service Quality (LSQ), which is divided into Relational Logistics Service Quality (RLSQ) and Operational Logistics Service Quality (OLSQ), on customer satisfaction, trust, service commitment, and customer loyalty in the B2B logistics sector. A quantitative research methodology was employed, collecting data from 250 customers of logistics service providers and analyzing the data using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that RLSQ and OLSQ positively influence customer satisfaction, with OLSQ having a particularly strong impact on trust and service commitment. Additionally, customer satisfaction directly affects trust and loyalty, both in attitudinal and behavioral dimensions. Furthermore, trust and service commitment significantly enhance customer loyalty, as customers who perceive high-quality service and commitment from providers are more likely to continue using the service and are less likely to switch to competitors. The study suggests that logistics service providers should improve service quality in both relational and operational aspects, enhance trust and commitment through transparency and service consistency, and promote attitudinal loyalty through customer engagement programs. Future research should expand the scope to B2C logistics and e-commerce-related industries and explore the impact of emerging logistics technologies, such as AI, Blockchain, and IoT, in enhancing service efficiency and gaining a competitive advantage.